THE DYNAMICS OF INDONESIA'S REJECTION OF THE FRAMEWORK CONVENTION ON TOBACCO CONTROL (FCTC) RATIFICATION: A TWO-LEVEL GAMES THEORY ANALYSIS - Dasep, Muhamad (Kajian Asia Pasifik, 2024)
This research will examine the reasons why Indonesia has not ratified the Framework Convention on Tobacco Control (FCTC) into its Tobacco Control policy in Indonesia. Indonesia is one of the largest tobacco producing countries in the world with a large number of smokers and a large tobacco industry. A study by the Indonesian Ministry of Health found that tobacco-related deaths increased from 190,260 in 2010 to 240,618 in 2013. Initially, Indonesia was one of the 20 full drafting members for the formation of the FCTC since its initial formulation in 1996. However, until now Indonesia has become one - the only country in Southeast Asia that has not ratified the Framework Convention on Tobacco Control (FCTC) into its Tobacco Control policy in Indonesia. Using Robert Putnam's Two Level Games Theory, the aim is to see the interaction between level 1 (international level) and level Il (domestic level). The research results show that the Indonesian government did not ratify the FCTC because the level II win-set size was small and did not overlap. Clearer national economic considerations for the tobacco sector as well as strong lobbying from related interest groups are the main factors in rejecting ratification. Therefore, this paper seeks to explain the research question: "Why does Indonesia not ratify the Framework Convention on Tobacco Control (FCTC)?". This research uses secondary data collection methods, namely through books, journals and documentation.